1962
DOI: 10.1136/gut.3.1.65
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of a series of newer anticholinergic agents with atropine as regards their effect on saliva flow and gastric secretion in man

Abstract: SYNOPSISThe effect of anticholinergic agents-atropine, propantheline, oxyphencyclimine, and propionyl atropine methyl nitrate-on saliva flow and on hypoglycaemic stimulated gastric secretion has been studied. The acid secretion of the nervous phase of gastric secretion was inhibited by anticholinergic drugs. They influenced gastric secretion to a greater extent than saliva flow.Both propantheline and oxyphencyclimine have a selective action on the stomach superior to atropine. Propionyl atropine methyl nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1964
1964
1986
1986

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Salivary flow measurements have previously beenused to estimate the duration of action and the time of maximal action of various anticholinergic agents, such as atropine (Mushin, Galloon, and Lewis-Faning, 1953), slowly released belladonna alkaloids (Reese, Free, Swintosky, and Grossman, 1959), and synthetic preparations (Grossman, 1958;Piper and Stiel, 1962;Juniper, Stewart, de Vancy, and Smith, 1964). The method described here differs in some respects from those used previously, over which it has several advantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary flow measurements have previously beenused to estimate the duration of action and the time of maximal action of various anticholinergic agents, such as atropine (Mushin, Galloon, and Lewis-Faning, 1953), slowly released belladonna alkaloids (Reese, Free, Swintosky, and Grossman, 1959), and synthetic preparations (Grossman, 1958;Piper and Stiel, 1962;Juniper, Stewart, de Vancy, and Smith, 1964). The method described here differs in some respects from those used previously, over which it has several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…In some of the previous comparative studies (Piper and Stiel, 1962;Juniper et al, 1964) various indices, including gastric secretion, have been measured at arbitrary time intervals after single standard doses of drugs. Since there is considerable individual variation in response, it is uncertain whether the doses of the different drugs used were 8 equivalent, so that such comparisons are of questionable validity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piper and Stiel compared the effect of oral preparations of atropine sulfate 0.7 mg, propantheline 30 mg, oxyphencyclimine 10 mg, and propionyl methyl nitrate 18 mg, on salivary flow and gastric acid secretion. They found that propantheline and oxyphencyclimine had a more selective action on acid secretion inhibition (20). Oxyphencylimine has the advantage over prophantheline of a more prolonged inhibitory action on acid secretion.…”
Section: Mechanism Of Actionmentioning
confidence: 98%
“…There is as yet , no evidence that anyone preparation has a longer duration than any other if given in doses equipotent at the time of maximal action. Adequate evidence exists that the newer proprietary preparations have a more selective action on the stomach than atropine (Piper and Stiel, 1962 ;Herrmann and Sulway, 1971) and it is hoped that with the further exploitation of this property an effective medical vagotomy will be possible.…”
Section: Clinical Pharmacology Of Anticholinergic Drugsmentioning
confidence: 98%